Is Decoupling in action? - Antonio Pesce (European Regional Science Association (ERSA), 2013)
Emerging market economies (also known as emerging economies, EEs) have become important on the world economic stage, where they now play a vital role in international trade and financial flows and account for a conspicuous fraction of the global economic dynamic. Despite the relatively tepid economic growth of advanced economies (AEs) from 2004 to 2007, the growth of EEs continued to be strong during that same period. This behaviour provided some evidence for the so-called ?decoupling hypothesis? that EEs have, over time, become less dependent on AEs. With the recent global financial crisis, the direction of the debate on the ?decoupling? has been partially changed; thus, the discussion remains unresolved. The decoupling hypothesis implies two main consequences. First, the comovement of economic cycles between AEs and EEs should decrease over time. Second, the resilience of the EEs to adverse scenarios in AEs should increase through time. This work sought to identify empirical evidences of the two consequences of decoupling. Two approaches were employed: 1) the Euclidean distance was used to evaluate the correlation of the international economic cycles, and 2) a time-varying Panel VAR model was used to decompose fluctuations in GDP into global, regional, group and country specific components and quantify the time path of the resilience of EEs. Although the Euclidean distance does not provide a clear indication in favour of decoupling, if we consider a sufficiently lengthy time period what does emerge, albeit subject to certain geographical differences, is that the connection between EEs and EAs has changed in that EEs are more resilient to the adverse scenarios that may arise in AEs. This result lends support to the decoupling hypothesis, although it is also clear that the process of strengthening of the EEs, that is, the decoupling process, has not emerged in a gradual, progressive manner, but has, on the contrary, followed a more complex dynamic characterised by ?alternate phases?. This discontinuity over time, together with the geographical peculiarities of the phenomenon, is still to be fully understood.
Keywords: C11; C33; E32; F44; 330; Economic Cycles; Emerging and Advanced Countries; Bayesian methods